2014
DOI: 10.3109/17435390.2014.894150
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine monophosphate is elevated in the bronchoalveolar lavage fluid of mice with acute respiratory toxicity induced by nanoparticles with high surface hydrophobicity

Abstract: Inhaled nanomaterials present a challenge to traditional methods and understanding of respiratory toxicology. In this study, a non-targeted metabolomics approach was used to investigate relationships between nanoparticle hydrophobicity, inflammatory outcomes and the metabolic fingerprint in bronchoalveolar fluid. Measures of acute lung toxicity were assessed following single-dose intratracheal administration of nanoparticles with varying surface hydrophobicity (i.e. pegylated lipid nanocapsules, polyvinyl acet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 46 publications
2
13
0
Order By: Relevance
“…Similar to previously published reports [15,16], lipid nanocapsule administration to the healthy lung was well tolerated. Importantly, nanocapsule administration to a murine model of neutrophilic airway inflammation did not to exacerbate the pre-existing inflammatory condition.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Similar to previously published reports [15,16], lipid nanocapsule administration to the healthy lung was well tolerated. Importantly, nanocapsule administration to a murine model of neutrophilic airway inflammation did not to exacerbate the pre-existing inflammatory condition.…”
Section: Discussionsupporting
confidence: 88%
“…procedure did not induce acute inflammation in healthy lungs (Fig. 1B-D), thus confirming previous findings [15,16]. Histological analysis of lung tissue showed an accumulation of neutrophils in the lungs obtained from mice pre-treated with LPS ( Fig.…”
Section: Lung Inflammationsupporting
confidence: 90%
See 2 more Smart Citations
“…Results confirm that particles with high surface hydrophobicity were proinflammatory and that adenosine monophosphate (AMP) concentration in bronchoalveolar fluid was correlated with neutrophilia and nanoparticle surface hydrophobicity. 17 Grabowski et al, 18 in a model of human respiratory alveolar epithelium cell culture, have clearly demonstrated that the inflammation and cell damage induced by these vectors are correlated with the surface charge and the nature of the nanoparticle core.…”
mentioning
confidence: 99%